Analysis of Student Problem Solving Skills in Harmonic Motion Materials - Fitroh, Ummi Nuzulul; Rusilowati, Ani; Darsono, Teguh; Marwoto, Putut; Mindyarto, Budi Naini (Universitas Negeri Semarang, 2020)
The purpose of this research is to analyze the problem solving ability of harmonic motion material. Problem solving skills are one of the important components of learning. Therefore, it is necessary to analyze the extent of student problem solving skills. The method used in this study is a descriptive analysis method with data collection techniques using the instrument of the description problem along with aspects of problem solving capability assessment. The subjects of this study were 24 physics education students who had obtained harmonic motion material. The results showed that students had difficulty in harmonic motion material. In the first phase of useful description, the average problem-solving ability of students was only 41.21%. The second stage of physics approach,the average student ability of 32.24%. The third phase of the specific application of physics, the average student's ability is only 14.21%. The fourth stage of mathematical procedure,student ability by 10.11%, the fifth stage of logical progession averages student ability by 2.23%. Therefore, it can be said that problem solving skills are still relatively low, so learning is needed that can improve students' problem solving skills. Based on the results of the analysis, it can be concluded that the most common mistakes made by students in solving physics problems are errors in the process of conveying results and assessing solutions. Mistakes that are rarely made by students are mistakes in understanding problems by using correct representations.